Predictors for Gingival Index in Middle-Aged Asian Indians with Type 2 Diabetes from South India: A Cross-Sectional Observational Study. (2nd January 2018) - Karthik, S. Jai; Anoop, Shajith; Kumar, R. Suresh; Rani, M. V. Usha
Abstract : Asian Indians develop type 2 diabetes mellitus (T2DM) much earlier as compared to White Caucasians, due to unique phenotypic and genetic architecture. Periodontitis in T2DM patients is often a neglected clinical feature. This study was conducted to derive predictor variables for gingival index in middle-aged Asian Indians with T2DM in a semiurban population of Dravidian ethnicity from Tamil Nadu, India. T2DM patients (n = 232, mean age:50 . 6 ± 10 . 4 years) with periodontitis (n = 123, mean age:54 . 3 ± 2 . 4 years) and without periodontitis (n = 109, mean age:55 . 2 ± 3 . 1 years) were recruited between 2014 and 2016 by purposive sampling method. Dental examinations for pocket depth (PD) and clinical attachment level (CAL) were performed and gingival index was calculated. Fasting venous blood samples were analysed for measures of glycaemia and cholesterol. Significant positive correlation (p < 0 . 01 ) was observed for gingival index with glycosylated haemoglobin (HbA1c), pocket depth, presence of T2DM, and clinical attachment level. Stepwise multiple linear regression analysis derived increased pocket depth (p < 0 . 01 ), elevated HbA1c (p < 0 . 01 ), clinical attachment level (p < 0 . 01 ), and presence of diabetes (p < 0 . 01 ) as significant predictors (r 2 value = 0.67) for increased gingival index in middle aged patients with T2DM. These variables significantly (p < 0 . 01 ) predispose middle-aged T2DM patients to increased gingival index, thus warranting appropriate intervention.